Disentangling cross-border interactions. Issue 4 (17th September 2019) - Grainger, Andrew; Morini, Cristiano
Abstract : Purpose: The purpose of this paper is to disentangle the interactions between logistics operators and government stakeholders in cross-border logistics operations with a specific focus on the UK and Brazil. Design/methodology/approach: The research builds on supporting literature. The comparative cases of the UK and Brazil are examined by reference to an extensive series of focus group workshops as well as a series of interviews with key informants. Care was taken to make sure that comprehensive engagement the respective business and government communities were in place, and that there were opportunities to feedback on the analysis. Findings: Suggestions were provided on how to improve the business–government interactions in cross-borders logistics operations. The analysis considered transaction costs and scope for trade facilitation. The research also helped produce a descriptive model of business–government interactions in cross-border logistics operations. Research limitations/implications: The paper points to new directions in the understanding of how businesses interact with government agencies, and the kind of issues they face in cross-border logistics operations. However, the research only looked at two countries and there is significant scope for further enquiry within the logistics literature. Practical implications: Reduced transaction costs at the border and subsequent economic opportunities for the UK and Brazil. Social implications: A list of practical reform recommendations informed by the business communities of the UK and Brazil. Originality/value: This paper's original contribution to the literature is its framework for the analysis of transaction costs associated with the business–government interactions in cross-border logistics operations. In addition to the resulting findings in Brazil and the UK it may serve as a template for research elsewhere.